To solve the equation \( F = \frac{9}{5}C + 32 \) for \( C \), let's follow the correct steps:
-
Start with the equation: \[ F = \frac{9}{5}C + 32 \]
-
Subtract 32 from both sides: \[ F - 32 = \frac{9}{5}C \]
-
Now, to isolate \( C \), multiply both sides by \( \frac{5}{9} \): \[ C = \frac{5}{9}(F - 32) \]
This simplification results in: \[ C = \frac{5}{9}F - \frac{160}{9} \]
So, let's evaluate the options based on this process:
A. First step is to multiply by 9 on each side. - False (The first step is to subtract 32.)
B. First step is to add 32 to both sides. - False (It should be subtracting 32.)
C. The next step from \( F - 32 = \frac{9}{5}C \), could be to multiply both sides by 5. - False (The correct step is to multiply by \( \frac{5}{9} \).)
D. The next step from \( F - 32 = \frac{9}{5}C \), could be to divide both sides by 5. - False (The correct step is to multiply by \( \frac{5}{9} \).)
E. Solution: \( \frac{5}{9}F - 32 = C \) - False (The correct solution is \( C = \frac{5}{9}(F - 32) \).)
F. To solve this equation for C, you would have to distribute at some point. - True (In the final step, distribution would occur when expressing \( C \) as \( C = \frac{5}{9}F - \frac{160}{9} \).)
Thus, the only true statement is:
- F. To solve this equation for C, you would have to distribute at some point.